Proton-conducting poly(ether sulfone ketone)s containing a high density of pendant sulfonic groups by a convenient and mild post-sulfonation. Issue 40 (19th September 2018) - Wang, Chenyi; Zhou, Yuanpeng; Shen, Bin; Zhao, Xiaoyan; Li, Jian; Ren, Qiang
Abstract : A class of new poly(ether sulfone ketone)s containing a high density of pendant sulfonic groups on the sulfonated structural units were designed and the resulting membranes exhibited overall good performance at low IEC levels. Abstract : Aromatic sulfonated polymers are a class of important proton exchange membranes. With the aim of further enhancing their properties at low levels of ion-exchange capacity (IEC), a class of new poly(ether sulfone ketone)s containing multiple sulfonic acids on the side chains of the sulfonated structural units (sPh-PESK- xx ) were designed and prepared by a convenient and mild post-sulfonation reaction process. The structures of the related monomer and copolymers were confirmed by IR and NMR analysis. The resulting membranes from solution casting of these aromatic sulfonated polymers showed overall good performance at low IEC levels. Their proton conductivities were in the range of 110–154 mS cm −1, while their swelling ratios were in the range of 6.2%–16.1% at 80 °C. Meanwhile, they also displayed good thermal and chemical oxidative stabilities. The results confirmed that the incorporation of a high density of pendant sulfonic groups is an effective way to improve the performance of aromatic sulfonated polymers.